2015
DOI: 10.1002/app.42915
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of poly(lactic acid) based nanocomposites: Effects of different organoclay modifiers and compatibilizers

Abstract: Poly(lactic acid) (PLA) nanocomposites containing five types of organically modified, layered silicates and two elastomeric compatibilizers, namely ethylene‐glycidyl methacrylate (E‐GMA) and ethylene‐butyl acrylate‐maleic anhydride (E‐BA‐MAH), were prepared using a twin screw extruder. The morphologies of the nanocomposites were determined by X‐ray diffraction (XRD) and transmission electron microscopy (TEM), and the rheological properties of the melts were measured using small‐amplitude oscillatory shear. XRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The difference in the morphologies of E-GMA and E-BA-MAH containing nanocomposites is reflected in both mechanical and rheological properties, and the latter is discussed in another publication. 30 In that study, the apparent shear-thinning observed in PLAorganoclay nanocomposites containing E-BA-MAH was attributed to weaker interactions between MAH and PLA, as compared to GMA and PLA.…”
Section: Scanning Electron Microscopymentioning
confidence: 84%
“…The difference in the morphologies of E-GMA and E-BA-MAH containing nanocomposites is reflected in both mechanical and rheological properties, and the latter is discussed in another publication. 30 In that study, the apparent shear-thinning observed in PLAorganoclay nanocomposites containing E-BA-MAH was attributed to weaker interactions between MAH and PLA, as compared to GMA and PLA.…”
Section: Scanning Electron Microscopymentioning
confidence: 84%
“…With the addition of the clay to the PLA/BioPE blend the slopes (shown in Fig. 5b) of the curves at the terminal zone substantially decreases and the G 0 is almost independent of the frequency, indicating that the behavior is changed from liquid-like to solid-like, which may be ascribed to the formation of a percolated network structure [26]. Figure 5c shows the damping factor (tan d) as a function of temperature.…”
Section: Rheological Properties Under Dynamic-oscillatorymentioning
confidence: 97%
“…The addition of E‐GMA introduces a solid‐like rheological behavior at low frequencies. All of the nanocomposites have similar rheological behavior at high frequencies …”
Section: Reinforcing Pla‐based Materials Through Nanocompositesmentioning
confidence: 98%
“…All of the nanocomposites have similar rheological behavior at high frequencies. [41] Graphite/carbon-based composites Carbonaceous nanocomposites like CNT, graphite, and carbon black have been extensively investigated nanofillers. They enhance mechanical resilience and thermal/electrical conductivity.…”
Section: Reinforcing Pla-based Materials Through Nanocompositesmentioning
confidence: 99%